A Case report of hemodynamic instability, cardiac arrest, and acute severe dyspnea subsequent to inhalation of crystal methamphetamine - Farhad Gholami; Seyed Hamzeh Hosseini; Amirhossein Ahmadi; Maryam Nabati (Mazandaran University of Medical Sciences, 2019)
Misuse of stimulants similar to amphetamine is a universal problem. These stimulants cause many complications in their abusers. However, myocardial infarction is rarely reported as a complication of amphetamine abuse. Herein, we report a man aged 42 years presented at the Emergency Department with the chief complaint of acute dyspnea following ice inhalation without history of dyspnea. Within the first hour and a half of admission, the patient was treated by nasal oxygen and bronchodilator aminophylline. However, he did not respond to the initial treatment and lost his consciousness; showed ventricular fibrillation, cardiac arrest, and hemodynamic instability. So, cardiopulmonary resuscitation was immediately initiated for him. The patient was intubated, mechanically ventilated. Also, the synchronized electrical shock was delivered 5 times (200-360 J) along with amiodarone (300 mg intravenously [IV] stat, then 1 mg/min IV infusion for 6 hours and next 0.5 mg/min for 18 hours) to treat the ventricular fibrillation. The arrhythmia was subsequently controlled, and his normal sinus rhythm was resumed. Two hours later, condition of the patient improved, and he was extubated. After two days, when the patient got stable, the echocardiography was performed, which was completely normal.